Thrombolytic, Membrane Stabilizing and Hypoglycemic Activities of Anethum sowa Linn. - Mansur, Muhammad Abdullah Al; Siddiqi, M Mahboob Ali; Saha, Koushik (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The hexane (HE), dichloromethane (DCME), ethyl acetate (EAE) and methanol (ME) extracts of seed and stem of Anethum sowa were subjected to screenings for thrombolytic, membrane stabilizing and hypoglycemic activities. Ethyl acetate extract of stem showed highest thrombolytic activity. In addition, the dichloromethane, ethyl acetate and methanol extract of seed revealed higher percentage (%) of inhibition in hypotonic solution induced hemolysis. In hypoglycemic activity, the dichloromethane and ethyl acetate extracts of stem and seed displayed significant blood glucose lowering effect. Dhaka Univ. J. Pharm. Sci. 17(2): 237-241, 2018 (December)